Pathology in Ecological Research With Implications for One Health: Session Summary. (December 2019) - Haschek, Wanda M.; Berenbaum, May; Hinton, David E.; Cora, Michelle; Chernoff, Neil; Travlos, Gregory; Liu, Chih-Wei; Lu, Kun; Law, Mac
This session explored the effects of pollutants on One Health at the ecosystem level that included microbes, insects, fish, and humans. The concept of One Health seeks to synergize medical, veterinary, and other health science disciplines to more effectively advance human and animal health. Presentations explored the interactions of pesticides, pathogens, phytochemicals, and xenobiotic biotransformation in bee colony losses critical for food security (bees have been recently listed under the 2017 US Food and Drug Administration (FDA) veterinary feed directive); the role of pathology in identifying the effects of pollutants on fish as sentinels for human health; the effects in rats of per- and polyfluoroalkyl substances (PFAS) that can persist in the environment and contaminate drinking water; harmful algal blooms and toxin production leading to animal and human disease; and the processing of environmental carcinogens by intestinal microbiota.